Do high tariffs provide high efficiency: a case of Ukrainian electricity distribution companies - Гончарук, Анатолій Григорович; Гончарук, А. Г.; Гончарук, Анатолий Григорьевич; Honcharuk, Anatolii H.; Goncharuk, Anatoliy G.; Горобець, Тамара Анатоліївна; Горобець, Т. А.; Горобец, Тамара Анатольевна; Horobets, Tamara A.; Яцишин, Вадим Валерійович; Яцишин, В. В.; Яцишин, Вадим Валерьевич; et al. (IGSMiE PAN, 2020)
The paper aims to test the hypothesis whether high tariffs lead to a high efficiency of electricity suppliers. The authors test this hypothesis on a case of 29 Ukrainian electricity distribution companies. Using the data envelopment analysis and correlation coefficients, grouping the super-efficiency scores, the authors found that in most regions of Ukraine the increase in tariffs no longer leads to increased efficiency. This indicates a weakness of tariff policy in most of the electricity distribution companies. The case showed that rising tariffs can cause a decline in revenue, net income and an increase in accounts payable. This does not allow the electricity distribution companies to provide high efficiency. Apart from this, despite improving the financial performance of most companies, the electricity distribution industry in Ukraine as a whole remains unprofitable. However, the high percentage of foreign investors in this industry indicates a significant potential for increasing the efficiency of Ukrainian energy companies. The government control of the electricity distribution companies more often provides medium efficiency, while the management by foreign investors often provides a high efficiency. The absence of the major owner and the presence of blocking stakes in any investor (government, domestic or foreign investors) has a negative impact on the efficiency of energy companies. Although the case is limited to one country and 29 companies, this study can serve as a model for wider testing of the research hypothesis in other markets and countries.

Стаття прагне перевірити гіпотезу, чи призводять високі тарифи до високої ефективності постачальників електроенергії. Автори перевіряють цю гіпотезу на прикладі 29 українських електророзподільчих компаній. Використовуючи аналіз обсягу даних та коефіцієнти кореляції, групуючи оцінки суперефективності, автори виявили, що в більшості регіонів України збільшення тарифів більше не веде до підвищення ефективності. Це свідчить про слабкість тарифної політики у більшості компаній з розподілу електроенергії. Приклад показав, що зростання тарифів може спричинити зменшення доходів, чистого доходу та збільшення кредиторської заборгованості. Це не дозволяє електророзподільним компаніям забезпечити високу ефективність. Окрім цього, незважаючи на покращення фінансових показників більшості компаній, галузь розподілу електроенергії в Україні в цілому залишається збитковою. Однак високий відсоток іноземних інвесторів у цій галузі свідчить про значний потенціал для підвищення ефективності діяльності українських енергетичних компаній. Державний контроль за компаніями з розподілу електроенергії частіше забезпечує середню ефективність, тоді як управління іноземними інвесторами часто забезпечує високу ефективність. Відсутність основного власника та наявність блокуючих пакетів акцій у будь-якого інвестора (уряду, вітчизняних чи іноземних інвесторів) негативно впливає на ефективність енергетичних компаній. Хоча справа обмежена однією країною та 29 компаніями, це дослідження може послужити моделлю для більш широкого тестування гіпотези дослідження на інших ринках та в інших країнах.

Работа направлена ​​на проверку гипотезы о том, приводят ли высокие тарифы к высокой эффективности поставщиков электроэнергии. Авторы проверяют эту гипотезу на примере 29 украинских распределительных компаний. Используя анализ объема данных и коэффициенты корреляции, сгруппировав оценки сверхэффективности, авторы обнаружили, что в большинстве регионов Украины повышение тарифов больше не приводит к повышению эффективности. Это свидетельствует о слабости тарифной политики большинства распределительных компаний. Пример показал, что рост тарифов может вызвать снижение выручки, чистой прибыли и увеличение кредиторской задолженности. Это не позволяет электрораспределительным компаниям обеспечивать высокий КПД. Кроме того, несмотря на улучшение финансовых показателей большинства компаний, электроэнергетическая отрасль в Украине в целом остается убыточной. Однако высокий процент иностранных инвесторов в этой отрасли указывает на значительный потенциал повышения эффективности украинских энергетических компаний. Государственный контроль над электрораспределительными компаниями чаще обеспечивает среднюю эффективность, тогда как управление иностранными инвесторами часто обеспечивает высокую эффективность. Отсутствие крупного собственника и наличие блокирующего пакета у любого инвестора (государства, отечественных или иностранных инвесторов) отрицательно сказывается на эффективности энергетических компаний. Хотя случай ограничен одной страной и 29 компаниями, это исследование может служить моделью для более широкой проверки исследовательской гипотезы на других рынках и в других странах.
Goncharuk A. Do high tariffs provide high efficiency: a case of Ukrainian electricity distribution companies / A. Goncharuk, T. Horobets, V. Yatsyshyn, I. Lahutina // Polityka Energetyczna – Energy Policy Journal. – V. 23 (3). – IGSMiE PAN, 2020. – P. 125–134.
Keywords: electricity; energy distribution; efficiency; tariff policy; companies; Ukraine; електроенергія; розподіл енергії; ефективність; тарифна політика; компанії; Україна; электроэнергия; распределение энергии; эффективность; тарифная политика; компании; Украина; Research Subject Categories::SOCIAL SCIENCES::Business and economics